External validation of multidimensional prognostic indices (ADO, BODEx and DOSE) in a primary care international cohort (PROEPOC/COPD cohort) - Espantoso-Romero, Maite; Román Rodríguez, Miguel; Duarte-Pérez, Ana; Gonzálvez-Rey, Jaime; Callejas-Cabanillas, Pedro A; Lazic, Durdica Kasuba; Anta-Agudo, Berta; Torán Monserrat, Pere; Magallon-Botaya, Rosa; Biljana Gerasimovska-Kitanovska; Lingner, Heidrun; Assenova, Radost S; et al. (BMC Purt of Springer Nature, 2016)
Due to the heterogeneous and systemic nature of the chronic obstructive pulmonary disease (COPD), the new guidelines are oriented toward individualized attention. Multidimensional scales could facilitate its proper clinical and prognostic assessment, but not all of them were validated in an international primary care cohort, different from the original ones used for model development. Therefore, our main aim is to assess the prognostic capacity of the ADO, BODEx and DOSE indices in primary care for predicting mortality in COPD patients and to validate the models obtained in subgroups of patients, classified by revised Global Initiative for Chronic Obstructive Lung Disease (2011) and updated Spanish Guideline (2014). Besides, we want to confirm that the prognostic capacity of all indices increases if the number of exacerbations is substituted by the interval between them and to assess the impact on health of the patient's lifestyle, social network and adherence to treatment.